Halal food in the perspective of Consumer Law Protection - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2024)
Indonesia is a muslim majority country in the world. As Muslims, it is mandatory to comply with religious prohibitions that must be obeyed, namely by not consuming food and drinks (food) that are made/have kandungantidak halal. Several laws, namely: Consumer Protection Law, Health Law, Food Law and Halal Product Guarantee Law(UUJPH)are a form of legal protection for halal food products that can provide guarantees for consumption by Indonesian muslim communities.This paper is a descriptive qualitative that seeks to provide an overview of the problems of regulation of halal food products in relation to consumer protection and legal protection of consumers in consuming halal food products. The results of this study that the regulation of halal food products for companies or business actors who will trade their products in Indonesia based on Uujphif associated with consumer protection has provided legal certainty for the consumer community (Muslims) to consume halal food, namely with Halal Certification Marks and Halal labels. Likewise, several laws and regulations concerning halal food products that have been enacted provide legal protection for consumers in consuming food and drinks. Consumers must get information, safety and security of a food product that will be consumed in accordance with their choices.